EVALUASI PROGRAM PELATIHAN KEARSIPAN BERDASARKAN MODEL CIPP DI KANTOR WILAYAH KEMENTRIAN AGAMA PROVINSI SULAWESI UTARA - Basri Seenong; Sitti Mania; Muhammad Nur Akbar Rasyid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to evaluate the Archival Training Program at the Regional Office of the Ministry of Religious Affairs of North Sulawesi Province using the Context, Input, Process, Product (CIPP) evaluation model to provide a comprehensive assessment of program needs, resource readiness, implementation processes, and outcomes. A qualitative evaluative approach was employed. Data were collected through in-depth interviews, observations, and document analysis involving the Head of the Administrative Division, training organizers, resource persons, archival officers, and training participants. Data were analyzed using the Miles and Huberman interactive analysis model, consisting of data reduction, data display, and conclusion drawing. The trustworthiness of the findings was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that, in the context dimension, the program was implemented to address organizational needs for improving employees’ competencies in managing conventional and digital records. In the input dimension, the program was supported by competent trainers, relevant learning materials, adequate facilities, and strong organizational support, although greater emphasis on digital records management remains necessary. In the process dimension, the training was conducted according to the planned schedule through lectures, discussions, simulations, and practical sessions; however, limited practice time and variations in participants’ prior competencies posed challenges to optimal learning. In the product dimension, the program enhanced participants’ knowledge, technical skills, and application of archival management practices, contributing to more systematic records management and improved administrative performance. Overall, the Archival Training Program was found to be effective based on the CIPP evaluation model. The study recommends strengthening digital records management content, expanding practical learning opportunities, and implementing continuous post-training monitoring and evaluation to ensure the sustainability and long-term effectiveness of the program.